The Relationship Between Exercise Intention and Exercise Behavior of Junior School Students: An Analysis of Chain Mediating Effect - Chen, Yue; Yao, Shu-Jun; Ma, Qi-Shuai; Shao, Wei; Liu, Chao; Guo, Ke-Lei (Frontiers in Psychology, 2022)
Objective This study explores the relationship between exercise intention and exercise behavior and constructs a chain mediating model through the mediating effect of implementation intention and self-identity. Method Through the stratified cluster sampling method, 1,573 junior school students (with an average age of 13.71 ± 0.891 years) were evaluated by the exercise intention scale, the implementation intention scale, the self-identity scale, and the physical exercise grade scale. For data analysis, the common method deviation test, Pearson correlation analysis, and Model 6 in the SPSS macro program compiled by Hayes for the chain mediating test were conducted. Results (1) There is a marked correlation between positive exercise intention and exercise behavior (r = 0.345, p < 0.01), and exercise intention has a significant effect on the direct path of exercise behavior (β = 0.162, t = 12.355, p < 0.01). (2) Exercise intention can positively predict implementation intention (β = 0.219, t = 10.006, p < 0.01) and self-identity (β = 0.160, t = 16.159, p < 0.01); implementation intention can significantly and positively predict exercise behavior (β = 0.230, t = 12.742, p < 0.01),and self-identity can significantly and positively predict exercise behavior (β = 0.273, t = 7.911, p < 0.01). (3) Implementation intention and self-identity play a significant mediating role between exercise intention and exercise behavior. The mediating effect consists of three indirect effects: exercise intention → implementation intention → exercise behavior (the mediating effect value is 0.050), exercise intention → self-identity → exercise behavior (the mediating effect value is 0.044), and exercise intention →implementation intention → self-identity → exercise behavior (the mediating effect value is 0.017). Conclusion (1) Exercise intention can significantly and positively predict exercise behavior. (2) Implementation intention and self-identity exert a significant mediating effect between exercise intention and exercise behavior, including the separate mediating effect of implementation intention and self-identity, as well as the chain mediating effect of implementation intention and self-identity.